Effect of concentrated Butt-Joints on flexural properties of laminated Bamboo-Timber flitch beams. (February 2022) - Zhang, Hexin; Gharavi, Niaz; Wong, Simon HF; Deng, Yu; Bahadori-Jahromi, Ali; Limkatanyu, Suchart; Qiao, Yao; Kuang, JS
This paper presents the experimental and analytical studies to investigate the effect of concentrated butt-joints on the flexural properties of laminated bamboo-timber flitch beam (BTFB, or bio-flitch beam). The experimental results reveal that the concentrated butt-joints significantly reduce the flexural strength of the BTFB. They also suggest that the failure mechanism of the BTFB with or without concentrated butt-joints are completely different but less evidence shows an obvious effect of the butt-joints on the modulus of elasticity in bending. In addition, laminated bamboo lumber with concentrated butt-joints is found to be unsuitable for structural applications. The analytical predictions are in close agreement with the experimental results that demonstrate the potentials of the proposed analytical model as a forensic investigation instrument to estimate the strength reduction of the structure, if the butt-jointed laminated bamboo was, unfortunately, used in construction.